CHARACTERISATION AND ANTICOAGULANT ACTIVITY OF ZINC NANOPARTICLES SYNTHESISED FROM TURBINARIA SP - Sumedha Balaji, Dr.Abirami Arthanari (Chelonian Research Foundation, 2023)
Introduction: Nanotechnology has emerged as a promising field in the development of new therapeutic agents and materials with many applications in medicine.ZnNPs were synthesized using a green and environmentally friendly approach involving Turbinaria sp. as a reducing agent and stabilizer. Turbinaria is a genus of seaweed found mostly in tropical marine waters. It usually grows on stony substrates. Tropical species of Turbinaria, which are often consumed by herbivorous fish and echinoids, have relatively low phenolic and tannin content. Materials and methods: The Turbinarila sp. Was dried and the extract was prepared. The prepared plant extract was mixed with an equal quantity of zinc nanoparticle extract. The prepared extract was used to characterize the presence of zinc nanoparticles and its anticoagulant activity. Results: Characterization of the synthesized ZnNPs was carried out using various techniques including UV-visible spectroscopy, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDAX). The results confirmed the successful synthesis of spherical ZnNPs with a nanometer average size.In addition, Turbinaria sp. The anticoagulant activity of the -derivative ZnNPs was evaluated using in vitro coagulation tests. ZnNPs showed dose-dependent anticoagulant properties, significantly increasing the clotting time compared to control samples. These results indicate that ZnNPs can be developed as an anticoagulant with potential therapeutic applications. Conclusion: In conclusion, the ecological synthesis of zinc nanoparticles by Turbinaria sp. shows that it is possible to use natural resources to produce nanomaterials with valuable biomedical properties. The anticoagulant effect of these nanoparticles promises their use in various medical applications, such as the prevention and treatment of thrombosis, which opens new avenues for nanomedical research. Further studies are warranted to elucidate the molecular mechanisms underlying their anticoagulant activity and to assess their safety and efficacy in vivo. Keywords: Turbinaria sp. , Anticoagulant activity, FTIR analysis, EDAX analysis, SEM analysis, UV wavelength characterisation